2008
DOI: 10.1007/s12221-008-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Small diameter Polyurethane vascular graft reinforced by elastic weft-knitted tubular fabric of polyester/spandex

Abstract: Small diameter vascular grafts were fabricated from pure Polyurethane (PU) as well as PU reinforced with a tubular weft-knitted fabric. The tensile properties of the reinforced composite vascular grafts were compared with that of the tubular fabric itself and the pure PU vascular grafts. The elasticity and strength of the reinforced vascular grafts were improved compared with the tubular fabric. Strength of the reinforced vascular grafts was 5-10 times of the strength of the pure PU vascular grafts. Expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Improvements have been achieved with polyurethane-based materials, where tubular constructs have shown enhanced compliance over the currently used synthetic grafts [6]. Xu et al [7] fabricated small diameter vascular grafts using polyurethane reinforced with a tubular weft-knitted fabric. Although the tensile properties of the reinforced grafts were improved compared with the pure polyurethane constructs, these grafts required a very specific weft-knitting machine to fabricate the knitted tube, and therefore reproducibility becomes a concern.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements have been achieved with polyurethane-based materials, where tubular constructs have shown enhanced compliance over the currently used synthetic grafts [6]. Xu et al [7] fabricated small diameter vascular grafts using polyurethane reinforced with a tubular weft-knitted fabric. Although the tensile properties of the reinforced grafts were improved compared with the pure polyurethane constructs, these grafts required a very specific weft-knitting machine to fabricate the knitted tube, and therefore reproducibility becomes a concern.…”
Section: Introductionmentioning
confidence: 99%
“…However, the histocompatibility of modified PU material varies when mixed with various SF powders at different ratio. A composite of superfine SF powder and PU material at a ratio of 1 : 1 had mechanical properties close to those of human arteries, and at this ratio the histocompatibility of the material was optimal . SF–PU (1 : 1) also showed a better histocompatibility in the acute phase than some established macromolecule biomaterials, such as Dacron, pure PU, and e‐PTFE .…”
Section: Discussionmentioning
confidence: 90%
“…Preliminary results suggested that the small diameter SF–PU graft reinforced with elastic tubular fabric had appropriate flexibility and enhanced physical properties close to human blood vessels …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This design concept improved the development of vascular grafts, which may be fabricated to be microporous and elastomeric, coaxial or triple‐tubular, using different types of materials with complementary properties. A coaxial three‐layer polyurethane vascular graft reinforced by weft‐knitted tubular fabric has been successfully fabricated via phase separation technique in our laboratory for improving suture and mechanical properties 28–30. The aim of this study was to investigate the effect of weft‐knitted tubular fabric on the radial mechanical property of the coaxial three‐layer polyurethane vascular grafts.…”
Section: Introductionmentioning
confidence: 99%